Penerapan Bauran Pemasaran Olahan Kopi di Data Coffee Kota Bandung - Rachman, Muhammad Alfi; Rochdiani, Dini; Rachmawati, Erna; Wulandari, Eliana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
There has been an increase in the trend of people spending time at coffee shops. Bandung is one of the cities where the food and beverage industry is growing rapidly and has become a central hub for coffee shop businesses in West Java. This rising trend requires coffee shops to be competitive within the same market scope, necessitating good management and marketing strategies. The purpose of this study is to analyze and describe the marketing mix that has been implemented by Data Coffee. In this research, the researcher uses descriptive analysis to describe the marketing mix coffee based product that has been implemented. The method used in this study is a case study method with a qualitative approach, and data collection techniques include observation, interviews, and documentation. The results of this study indicate that the marketing mix applied at Data Coffee is quite good, but there are still issues in several aspects of the marketing mix that need improvement and further development.